Developing and implementing new safe practices: voluntary adoption through statewide collaboratives. Issue 4 (2nd August 2006) - Leape, L L; Rogers, G; Hanna, D; Griswold, P; Federico, F; Fenn, C A; Bates, D W; Kirle, L; Clarridge, B R
Abstract : Background: Disseminating new safe practices has proved challenging. In a statewide initiative we developed a framework for (1) selecting two safe practices, (2) developing operational details of implementation, (3) enlisting hospitals to participate, and (4) facilitating implementation. Methods: Potential topics were selected by a multistep process to identify candidate practices, review the evidence for efficacy and feasibility, and then select them on the basis of importance, efficacy, feasibility, and impact. A multi-stakeholder advisory group representing all constituencies selected two practices: reconciling medications (RM) and communicating critical test results (CTR). Operational details and strategies for implementation were then developed for each practice using a consensus process of discipline stakeholders led by content experts. Hospital CEOs were solicited to participate by the Massachusetts Hospital Association which made the project a "flagship" initiative. A collaborative model was used to facilitate implementation, following the IHI Model for Improvement. In addition to providing exposure to content and method experts, we gave teams a "toolkit" containing recommendations, a change package, and implementation strategies. Each collaborative met four times over an 18 month period. Results were assessed using the IHI team assessment scale and surveys of teams and hospital leaders. Results: Hospital participation rate was high with 88% of hospitals participating in one or both collaboratives. Partial implementation of the practices was achieved by 50% of RM teams and 65% of CTR teams. Full implementation was achieved by 20% of teams for each. Conclusions: Major factors leading to hospital participation included the intrinsic appeal of the practices, access to experts, and the availability of implementation strategies. Team success was correlated with active engagement of a senior administrator, engagement of physicians, increased use of PDSA cycles, and attendance at collaborative meetings. The prior development of subpractices, recommendations and implementation strategies was essential for the hospital teams. These should be well worked out before hospitals are required to implement any guideline.